An Exploratory Pilot Study on Choking Episodes in Archery - Diotaiuti, Pierluigi; Corrado, Stefano; Mancone, Stefania; Falese, Lavinia; Dominski, Fábio Hech; Andrade, Alexandro (Frontiers in Psychology, 2021)
The aim of our study is to test the fit of an explanatory model of the frequency of the phenomenon of choking under pressure in archers, focusing on both the individual components (anxiety, coping styles, and decentralization) and environmental components (perception of coach assistance). 115 competitive athletes including 72 males (62.6%) and 43 females (37.4%) participated in the study, with average age of 39 years (±15.47). Participants reported personal data and completed measures of self-consciousness, anxiety, coping styles, and decentering. The ruminative component of concern was found to be the factor directly influencing the frequency of choking episodes in performance. Two significant mediations of personal coping style were also identified on the effects of anxiety on brooding thinking and on the athlete’s ability to decentralize. The latter personal self-regulative component has been shown to be able to strongly limit the frequency of choking under pressure. Finally, among the environmental components, a further facilitating influence for the athlete resulted in the perception of being supported by the coach. The results therefore suggest that the athlete in choking should not face alone the hard upcoming period, but should preferably be supported with an articulated program focused on the cognitive remodeling of disturbing thoughts, on the strengthening of the capacity of decentralization, on the enhancement of the relationship of support and trust with the coach.